Microbiological Quality and Antibiogram of E. coli, Salmonella and Vibrio of Salad and Water from Restaurants of Chittagong - Nawas, T; Mazumdar, RM; Das, S; Nipa, MN; Islam, S; Bhuiyan, HR; Ahmad, I (Journal of Environmental Science and Natural Resources, 2012)
The study aimed at examining the microbial quality of restaurant salad and the water used for salad preparation and their role as a source of antibiotic resistant bacteria. Samples were collected from 15 different restaurants located in Chittagong city. The range of Total Viable Count was 1.86×104 to7.28×105 CFU/g and 1.60×104 CFU/ml to 4.38×105 CFU/ml for salad and water respectively. Total colifrm and fecal coliform count > 1100 CFU/100 ml were found in 73.33% of salad and 33.33% water samples. Salmonella spp was present in 46.67% of restaurants salad and water. Vibrio spp. was present in 66.67% of salad and 53.33% of water. A total of 102 isolates belonging to genus Vibrio, Salmonella and E. coli were subjected to antibiotic sensitivity test by disc diffusion method by using nine different types of antibiotic discs. Salmonella spp. from salad and water showed resistance against Amoxicillin (75%), Cephradine and Cephalexin (68.75%). 85.71% Vibrio spp. isolated from salad and water were resistant to Amoxicillin respectively. Multiple drug resistance was seen in 39 and 51 isolates of Salmonella and Vibrio isolates, respectively. The results suggest the necessity to follow the hygienic practices in salad preparation and salad might have an important role as a source of multiple antibiotic resistant bacteria. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11571 J. Environ. Sci. & Natural Resources, 5(1): 159 - 166, 2012